Strains of Typhoid Salmonella in Pakistan Causing an Impending Threat for Drug-Resistant - Sehar Zahid, Sanaullah Khan, Muhammad Anwar, Arshad Rafeeq, Maria Haq, Shazia Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To estimate the resistant strains of enteric fever in Pakistan. Study Design: Cross sectional observation based study Place and Duration of Study: Department of Paediatric Medicine, Arif Memorial Teaching Hospital, Lahore from 1st April 2021 to 30th September 2021. Methodology: Fifty patients were selected as study participants. All those patients with positive culture for Salmonella typhi and paratyphi were included. The age of the enrolled patients was taken as >12 years. The microbiological testing for typhoid slides was performed after withdrawing 6cc blood from the patients for blood culturing. Results: The mean age of the patients was 28±5.3 years. Five patients who showed no resistance while 24% had multiple drug resistance and 66% had extensive drug resistance from various antibiotics against typhoid. Conclusion: Salmonella typhi is the main strain in Pakistan with extensive resistance found posing serious challenges in the treatment of the disease.